Reasons to doubt : wrongful convictions and the Criminal Cases Review Commission - Hoyle, Carolyn; Sato, Mai (Oxford : Oxford University Press, 2019)
This text reveals what happens to applications for post-conviction review when those in England and Wales who consider themselves to have been wrongfully convicted, and have exhausted direct appeal processes, apply to have their case assessed by the Criminal Cases Review Commission. It presents the findings of the first thorough empirical study of decision-making and the use of discretion within the Commission. It shows how the Commission exercises its discretionary powers in identifying and investigating possible wrongful convictions for rehearing by the Court of Appeal.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 4, 2019).
Keywords: Judicial error -- England; Judicial error -- Wales; Great Britain. -- Criminal Cases Review Commission; Law; Laws of specific jurisdictions & specific areas of law